2012
DOI: 10.2351/1.4718561
|View full text |Cite
|
Sign up to set email alerts
|

Nanogratings in fused silica: Formation, control, and applications

Abstract: The authors investigated the formation of periodic subwavelength structures, so-called nanogratings, in the volume of fused silica. These self-organized structures emerge upon irradiation with ultrashort laser pulses, undergoing three distinct stages of growth from randomly distributed nanostructures to extended domains with uniform periodicity. The experiments revealed that the cumulative action of subsequent laser pulses is mediated by dangling-bond type defects. On shorter time scales, transient self trappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 50 publications
(74 reference statements)
12
73
0
Order By: Relevance
“…3 represent the self-organized nanogratings found along the particular laser track. The periodicity of the self-organized patterns decreases as the number of pulses increases in-line with the observation by Shimotsuma et al [4] and subsequently by Richter et al [15] and Liang et al [7]. In addition to the reduced periodicity, the uniformity of the periodicity has also changed; higher energy deposition causes the lamellae to be discontinuous laterally across the modification zone.…”
Section: Self-organized Patternssupporting
confidence: 73%
See 1 more Smart Citation
“…3 represent the self-organized nanogratings found along the particular laser track. The periodicity of the self-organized patterns decreases as the number of pulses increases in-line with the observation by Shimotsuma et al [4] and subsequently by Richter et al [15] and Liang et al [7]. In addition to the reduced periodicity, the uniformity of the periodicity has also changed; higher energy deposition causes the lamellae to be discontinuous laterally across the modification zone.…”
Section: Self-organized Patternssupporting
confidence: 73%
“…If we assume the porosity found in nanogratings is homogeneous (which seems to be the case based on the observations from J. Canning et al [9], later confirmed by Richter et al [15]), considering the shape of the laser affected zones, we do expect high stress concentration to form near pronounced discontinuities, i.e. for instance at the tip of lamellae.…”
Section: Transition To Chaotic From Self-organizationmentioning
confidence: 96%
“…However, although great effort has been made on investigating the mechanism behind this phenomenon, a clear picture is still lacking until now [75,84]. Recently, it has been found that nanogratings can also be formed in a porous glass immersed in water by irradiation with femtosecond laser pulses of carefully selected pulse energies [37].…”
Section: Influence Of Ionization Property Of Immersion Liquidmentioning
confidence: 99%
“…1(a)). By tuning the laser parameters the structural properties and thus the birefringence can be controlled [3,4]. Consequently, there are numerous potential applications from phase elements controlling the laser polarization [3,4] to devices enabling the generation of optical vortices [5].…”
Section: Introductionmentioning
confidence: 99%